(untitled) (International journal of artificial intelligence, 2025)
This article analyzes the development and application of unmanned aerial vehicles from the early years of their development to World War II. During this period, the development of unmanned aerial vehicles was mainly observed in the developed countries of that era, in particular, Great Britain, the USA and the former Soviet Union. The article analyzes the needs and attempts to develop unmanned aerial vehicles in these countries.